How Malaria Parasites Acquire Nutrients From Their Host - Counihan, Natalie A.; Modak, Joyanta K.; de Koning-Ward, Tania F. (Frontiers in Cell and Developmental Biology, 2021)
Plasmodium parasites responsible for the disease malaria reside within erythrocytes. Inside this niche host cell, parasites internalize and digest host hemoglobin to source amino acids required for protein production. However, hemoglobin does not contain isoleucine, an amino acid essential for Plasmodium growth, and the parasite cannot synthesize it de novo. The parasite is also more metabolically active than its host cell and the rate at which some nutrients are consumed exceed the rate at which they can be taken up by erythrocyte transporters. To overcome these constraints, Plasmodium parasites increase the permeability of the erythrocyte membrane to isoleucine and other low-molecular weight solutes it requires for growth by forming new permeation pathways (NPPs). In addition to the erythrocyte membrane, host nutrients also need to cross the encasing parasitophorous vacuole membrane (PVM) and the parasite plasma membrane (PPM) to access the parasite. This review outlines recent advances that have been made in identifying the molecular constituents of the NPPs, the PVM nutrient channel and the endocytic apparatus that transports host hemoglobin and identifies key knowledge gaps that remain. Importantly, blocking the ability of Plasmodium to source essential nutrients is lethal to the parasite and thus components of these key pathways represent potential antimalaria drug targets.